Genome-wide CRISPR screens reveal cyclin C as synthetic survival target of BRCA2. Issue 13 (1st July 2021) - Tang, Mengfan; Pei, Guangsheng; Su, Dan; Wang, Chao; Feng, Xu; Srivastava, Mrinal; Chen, Zhen; Zhao, Zhongming; Chen, Junjie
Abstract: Poly (ADP-ribose) polymerase inhibitor (PARPi)-based therapies initially reduce tumor burden but eventually lead to acquired resistance in cancer patients with BRCA1 or BRCA2 mutation. To understand the potential PARPi resistance mechanisms, we performed whole-genome CRISPR screens to discover genetic alterations that change the gene essentiality in cells with inducible depletion of BRCA2. We identified that several RNA Polymerase II transcription Mediator complex components, especially Cyclin C (CCNC) as synthetic survival targets upon BRCA2 loss. Total mRNA sequencing demonstrated that loss of CCNC could activate the transforming growth factor (TGF)-beta signaling pathway and extracellular matrix (ECM)-receptor interaction pathway, however the inhibition of these pathways could not reverse cell survival in BRCA2 depleted CCNC-knockout cells, indicating that the activation of these pathways is not required for the resistance. Moreover, we showed that the improved survival is not due to restoration of homologous recombination repair although decreased DNA damage signaling was observed. Interestingly, loss of CCNC could restore replication fork stability in BRCA2 deficient cells, which may contribute to PARPi resistance. Taken together, our data reveal CCNC as a critical genetic determinant upon BRCA2 loss of function, which may help the development of novel therapeutic strategies that overcome PARPi resistance.